Системы энергоснабжения горной промышленности учебник для вузов - Крайнов, А. В. специалист в области теплотехники доцент Томского политехнического университета, кандидат физико-математических наук 1974- (Изд-во ТПУ, 2014)
The book contains the theoretical data, descriptions of contemporary energy systems of mining industry complex. The material of the book allows to get basic knowledge of the given systems and skills for calculating heat and electrical characteristics. The course book provides the necessary material for conducting classes and final tests. The combination of domestic and foreign technologies for teaching at high school is presented in the book. The book is intended for the students of mining specialities. The description comprehensiveness gives the possibility to use the course book in the scope of joint international education programs, in the system of elite technical education, professional development and self-study work.